Exports Versus FDI Revisited: Does Finance Matter - Monika Schnitzer; Claudia M. Buch; Iris Kesternich; Alexander Lipponer (Verein für Socialpolitik, 2010)
The crisis on international financial markets that started in 2007 has shown the potential links between the financial sector and the real economy. Exports and foreign direct investment (FDI) have declined, presumably not only because of a lack of demand, but also because of restricted access of firms to external finance. In this paper, we explore the impact of access to external finance on firms' choices to export or to engage in FDI. We simultaneously model a firm's decision to engage in FDI and in exports, and we assess the importance of financial factors for this choice (the extensive margin) as well as for the volume of activities (the intensive margin). We find that financial frictions matter, in particular for the decision to engage internationally.
Keywords: F23; F10; G20; 330; multinational firms; exports versus FDI; financial constraints; heterogeneity; productivity